THE IMPACT OF EMPLOYEE DISCIPLINE ON ORGANIZATION PERFORMANCE - Ibrahim Yinka AGBEYINKA (International Journal of Social and Educational Innovation)
In an organization, discipline guarantees efficiency and productivity. In addition to boosting employee morale, it promotes peace and cooperation among coworkers. The study evaluates how employee discipline affects organizational performance, specifically focusing on Polytechnic Ibadan. Because discipline is a practical tool for enhancing employee performance in an organization and for guiding employee behavior toward the achievement of organizational goals, the study found that an effective disciplinary system has a positive impact on organizational performance. Additionally, the study found that a well-functioning disciplinary system improves employees' compliance with organizational policies. According to the study, there is a connection between discipline and improved employee performance within the company, and an efficient disciplinary system is always a good way to boost productive employee performance. A disciplinary system increases employee motivation in an organization since severe staff indiscipline has a detrimental effect on productivity. As a reward for discipline, employees would stimulate employee performance and dedication to the organization. However, inferences from the study's results showed that the main factors undermining an effective disciplinary system in public organizations are ethnicity and nepotism, corruption, political affiliation and interference, favoritism, and the patronage system. This lowers the extent to which some errant employees are punished in the public sector, which inevitably affects productivity.